ADMINISTRATION IN KOKTURK KHANED INSCRIPTION: WORDS ESTABLISHED WITH VERBS - Özge EKER (Uluslararası Türk Lehçe Araştırmaları Dergisi, 2018)
In this study it will be try to constituted a conceptual field/frame of meaning in terms of their vocabulary that is constituted verbs in Kokturk Khaned Inscriptions. Verbs, which is reported act, occurance and manner are the most component, constituting a language. The multiplicity of actions and diversity are indicator circumstances of a language, Lifestyles of society reflect to their fundemental vocabulary. Also Kokturks have nomadic way of life. Also nomadic way of life of Kokturks reflected to three major inscription in eighth century. When look at Kokturk inscription, it is seen that a lot of acts. Providing easy axis of meaning in verbs, we can connect nomadic lifestyle of Kokturks. There are verbs, that the same meaning axis, but one with special meanings than the other. In this study, firstly it has been referred meaning of managing, to organize, to bring together verbs. We have tried to identified fundemental meaning of verbs. We have tried to sampled, the context where the same words, taking from three major inscriptions. Later we have tried to give a schema, frame of meaning that constituting this verbs. In this study, we tried to determine meaning frame of administration/manage also benefit hyponymy and hyperonymy topics.